Reliability and validity of a submaximal warm-up test for monitoring training status in professional soccer players - Rabbani, A.; Kargarfard, M.; Twist, C. (The Journal of Strength and Conditioning Research, 2018)
Two studies were conducted to assess the reliability and validity of a submaximal warm-up test (SWT) in professional soccer players. For the reliability study, 12 male players performed an SWT over 3 trials, with 1 week between trials. For the validity study, 14 players of the same team performed an SWT and a 30-15 intermittent fitness test (30-15IFT) 7 days apart. Week-to-week reliability in selected heart rate (HR) responses (exercise heart rate [HRex], heart rate recovery [HRR] expressed as the number of beats recovered within 1 minute [HRR60s], and HRR expressed as the mean HR during 1 minute [HRpost1]) was determined using the intraclass correlation coefficient (ICC) and typical error of measurement expressed as coefficient of variation (CV). The relationships between HR measures derived from the SWT and the maximal speed reached at the 30-15IFT (VIFT) were used to assess validity. The range for ICC and CV values was 0.83-0.95 and 1.4-7.0% in all HR measures, respectively, with the HRex as the most reliable HR measure of the SWT. Inverse large (r = -0.50 and 90% confidence limits [CLs] [-0.78 to -0.06]) and very large (r = -0.76 and CL, -0.90 to -0.45) relationships were observed between HRex and HRpost1 with VIFT in relative (expressed as the % of maximal HR) measures, respectively. The SWT is a reliable and valid submaximal test to monitor high-intensity intermittent running fitness in professional soccer players. In addition, the test's short duration (5 minutes) and simplicity mean that it can be used regularly to assess training status in high-level soccer players.